Climate and rapid local adaptation as drivers of germination and seed bank dynamics of Alliaria petiolata (garlic mustard) in North America. (20th October 2017) - Blossey, Bernd; Nuzzo, Victoria; Dávalos, Andrea
Summary: Local differences in climate conditions may facilitate rapid evolutionary changes in introduced plants to optimize timing of germination or ability to survive in seed banks, which may constitute beneficial demographic adaptations during range expansions. Understanding differences in germination requirements and emergence patterns across a species' range is critical for demographic modelling and potential invasive species control efforts. We assessed germination responses of Alliaria petiolata using seeds collected from 10 populations spanning much of the North American distribution of the species. We compared germination responses under different stratification regimes in a growth chamber over 2·5 years, and evaluated seedling emergence in a common garden in Ithaca, New York over 13 years. We further evaluated how climate overlap between Ithaca and original collection sites influenced emergence patterns. In the laboratory, germination of all populations was similar and highest at 4 °C stratification. Seeds exposed to sub‐zero temperatures delayed germination and population responses were variable. In the common garden, seedlings from most populations emerged over 13 years, and emergence patterns were strongly influenced by population. Annual emergence was positively correlated with spring temperature and inversely correlated with number of spring days with minimum temperature below freezing. Climate overlap between the common garden and original collection location enhanced germination, but common garden climate conditions over the course of the 13‐year experiment and population identity had greater explanatory power. Synthesis . Laboratory germination tests did not reflect seedling emergence under field conditions. After 150 years of residence time in North America, Alliaria petiolata populations have developed striking differences in their responses to local climates and stratification requirements suggesting that a complex interplay of pre‐adaptation, rapid evolutionary changes, and phenotypic plasticity result in locally adapted populations. Abstract : We document inter‐population variation in Alliaria petiolata germination and emergence pattern after 150 years of residence time in North America. Laboratory trials did not predict long‐term emergence pattern observed over 13 years in a common garden. Our data suggest that an interplay of pre‐adaptation, rapid evolutionary changes and phenotypic plasticity result in locally adapted populations.